Flashcards as Media to Students’ Achieve Vocabulary: Process and Role of Flashcard in Vocabulary Class - Susi Melani; Mansyur Srisudarso; Totoh Tauhidin (Peneliti.net, 2023)
This study aims to analyze the process in class with flashcards and the role of flashcards in learning vocabulary. The method of this research is the qualitative descriptive method that uses random sampling. This research was conducted in Senior High School in Karawang. The instruments of this research used observation and interviews to collect data. Other information, in analyzing the data of this study using the Interactive Model. The results obtained from this study are that flash cards make the class more productive, increase student motivation, increase student response rates, increase student participation, make students active and participatory enthusiastic in the learning process, increase students’ pronunciation, increase students’ fluency and increase students’ comprehension